Impact Empowerment and Work Environment on Employee Satisfaction of Ministry of Youth and Sports in Indonesia - Muhamad Arief Erdavit; Yetty Supriyati; Billy Tunas (Journal of International Conference Proceedings (JICP), 2019)
Employee satisfaction has become an issue in almost organizations in Indonesia. One who experienced the issue, the ministry of youth and sports became an interesting issue in Indonesia. The purpose of this study was to determine the effect of empowerment and work environment on employee satisfaction in the ministry of youth and sports. This study used 180 employees in the Ministry of Youth and Sports. The results show that empowerment has a significant and positive effect on job satisfaction by 0.457. The work environment also has a significant and positive effect on job satisfaction by 0.496. Therefore the ministry of youth and sports must focus on the work environment that has the most influence on job satisfaction.